Global electrification : multinational enterprise and international finance in the history of light and power, 1878-2007 - Hausman, William J.; Hertner, Peter; Wilkins, Mira; Cambridge eBooks (Cambridge : Cambridge University Press, 2008)
This book examines how multinational enterprises and international finance influenced the course of electrification around the world. Multinational enterprises played a crucial role in the spread of electric light and power from the 1870s through the first three decades of the twentieth century. However, their role did not persist, and by 1978 multinational enterprises in this sector had all but disappeared, replaced by electrical utility providers with national business structures. Yet, in recent years, there has been a vigorous revival. This book, a co-operative effort by the three authors and a group of experts from many countries, offers an analysis of the history of multinational enterprise. The authors take an integrated approach, not simply comparing national electrification experiences, but supplying a truly global account.
The invention and spread of electric utilities, with a measure of the extent of foreign ownership -- Multinational enterprise and international finance -- Every city, 1880-1914 -- War, the first nationalization, restructuring, and renewal, 1914-1929 -- Basic infrastructure, 1929-1945 -- Summary of the domestication pattern to 1978 -- coming full circle, 1978-2007, and a global perspective.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Electric utilities -- History; Electrification -- Economic aspects -- History; Power resources -- History; Electronic books